Molecular Möbius strips: twist for a bright future. Issue 15 (4th July 2022) - Yao, Bin; Liu, Xingyan; Guo, Tingwang; Sun, Hongfei; Wang, Wei
Abstract : In this article, the recent development of molecular Möbius strips will be highlighted, with an emphasis on the rational synthesis and the further investigations on their intriguing properties. Abstract : Due to their unique structural features and associated intriguing properties, molecular Möbius strips have attracted considerable attention. However, the precise synthesis of such attractive molecules remains a great challenge. Recently, relying on the rational design of suitable macrocyclic precursors and the development of a novel strategy as well as the assistance of theoretical calculations, the successful synthesis of diverse molecular Möbius strips, including both nonconjugated and conjugated ones, has been achieved. In addition, further investigations on the twist migration dynamics and topological chirality of these resultant molecular Möbius strips have also been performed. In this highlight, the recent advances in molecular Möbius strips are presented.